An evaluation of nutrition care to adult patients on Highly Active Antiretroviral Therapy (HAART) attending primary healthcare facilities in Mbombela North, Mpumalanga - Schiever, Jane Frances (Stellenbosch : Stellenbosch University, 2015)
Thesis (MNutr)--Stellenbosch University, 2015.